Extended Use of Chimeric Medial Sural Artery Perforator Flap for 3-Dimensional Defect Reconstruction. (January 2019) - Lee, Che-Hsiung; Chang, Nai-Jen Tommy; Hsiao, Jo-Chun; Chu, Yu-Ying; Lin, Chih-Hung; Kao, Huang-Kai; Lin, Cheng-Hung
Abstract : Background: The medial sural artery perforator (MSAP) flap has become increasingly popular because it is thin and pliable for small to moderate defect soft tissue reconstruction. Furthermore, chimeric MSAP flap, which includes a skin paddle and a separated piece of medial gastrocnemius muscle, allowed more freedom for flap insetting, especially in 3-dimensional defect reconstruction. Here we describe our experience regarding this clinical application. Patients and Methods: From 2007 to 2016, 14 male patients (average age, 46.9 ± 14.4 years) who received either a free or pedicled chimeric MSAP flap were included. Of these 14 patients, 7 received this flap for reconstruction in the head and neck, 2 in the upper extremities, and 5 in the lower extremities. Demographic data were collected and analyzed, and a literature review was performed. Results: Ten patients received free chimeric MSAP flap, and 4 received the pedicled type. Thirteen of the 14 flaps (92.6%) survived, and 1 failed 2 days later owing to venous insufficiency. Venous congestion-related partial loss occurred in another case. Conclusions: The chimeric MSAP flap is a good alternative for deep space obliteration or reconstruction of adjacent but separate defects in both free and pedicled flap design. Donor site morbidity is limited. However, the perforator needs to be mobilized carefully to prevent postoperative venous compromise.